Differences of antigenic profiles on immunoblotting of wild type measles virus and vaccine virus in Indonesia - Made Setiawan; Agus Sjahrurachman; Fera lbrahim; Agus Suwandono (Indonesian Pediatric Society, 2008)
Background Measles virus has a negative, single strand RNAgenome which codes for six important structural proteins. Thegenes of the wild type measles virus have many variances hencethe nucleotide sequences of each wild type virus and vaccine virusare different. This differences lead to the antigenic differencesbetween wild type and vaccine virus.Objective The purpose of this research is to investigate thedifferences in the antigenic profiles on immunoblotting betweenwild type and vaccine virus.Results The analysis results are 1) the antigen ofCAM-70 vaccinevirus was less able in cross reacting with the antibodies from G2,G3, 09, CAM-70 and Schwarz; 2) The antibody aga inst CAM-70 was only able to cross react with antigens of N protein and afew of antigens ofF proteins; 3) The wild type virus were veryimmunogenic, hence the antibody titers were very high; 4) TheCAM-70 and MMR vaccine virus were less immunogenic, hencetheir antibody were very low; 5) The antibody responses thatalways occurred from all immunized mice serum were antibodyfor N and F proteins. However, the antibody against CAM-70vaccine virus was still able to react with wild type virus (G2, G3and 09).Conclusion All antigen-antibody reaction on immunoblottingresulted in different profiles especially between wild type virusand CAM-70 vaccine virus. Although CAM-70 vaccine virusshowed clear differences compared to G2, G3 and 09 genotypes,antibodies against CAM-70 were still able to cross react withantigens from other genotypes (G2, G3 and D9).